(untitled) (Journal of Computational Mathematics, 2003)
The main purpose of this paper is to derive an explicit expression for Fourier-Chebyshev coefficient A_kn(f)=2π_-1^1f(x)T_kn(x)dx1-x^2 ,k,nN_0, which is initiated by L. Gori and C. A. Micchelli.